Pengaruh dimensi kompor dan kadar air biomassa terhadap kinerja kompor gasifikasi forced draft - Z Zulfansyah; H Hermanto; Muhammad Iwan Fermi (Jurnal Teknik Kimia Indonesia, 2013)
Influence of stove dimensions and biomass moisture content on forced draft gasification stove performanceConsumption level of biomass as a source of primary energy in Indonesia is quite high, reaching 280 million barrels of oil equivalent (BOE) and approximately 84% of the biomass is has been used for the household sector. The application of gasification stove especially in cooking purposes can increase the efficiency of fuel usage. This research uses three units gasification stove with variation of stove dimension. Acacia wood branches with moisture content 7.26%, 9.63% and 12.58% were used as fuel source. Water boiling test (WBT) procedural was used to evaluate the stove performance. Operating time and flame temperature of the stove also were the parameter of stove performance evaluation. Thermal efficiency of the forced draft gasification stove is approximately 25.03% to 30.44%, the most efficient is 12 cm in diameter and 16 cm high stove with 9.63% biomass moisture content. Although the resulting flame is still reddish yellow, the forced draft gasification stove is capable of producing up to 3.43 kWth (kilowatt thermal) thermal energy with the highest flame temperature reaches 933oC. The results show that the gasification stove operating conditions greatly affect the performance of the stove.Keywords: biomass, gasification stove, forced draft, thermal efficiency AbstrakTingkat penggunaan biomassa sebagai sumber energi primer di Indonesia cukup tinggi yaitu mencapai 280 juta setara barel minyak (SBM) dan sekitar 84% dari biomassa tersebut digunakan untuk kebutuhan sektor rumah tangga. Penggunaan kompor gasifikasi untuk kebutuhan rumah tangga khususnya untuk kegiatan memasak dapat meningkatkan efisiensi penggunaan bahan bakar. Pada penelitian ini digunakan tiga unit kompor gasifikasi dengan variasi dimensi ruang bakar kompor. Sedangkan bahan bakar yang digunakan yaitu ranting kayu akasia dengan kadar air 7,26%, 9,63% dan 12,58%. Metoda pengujian mengikuti prosedur water boiling test (WBT), selain itu waktu operasi dan temperatur nyala api juga menjadi parameter kinerja kompor gasifikasi yang dievaluasi. Efisiensi termal kompor gasifikasi forced draft yang dihasilkan yaitu 25,03% hingga 30,44%, dengan efisiensi tertinggi yaitu pada kompor berdiameter 12 cm dan tinggi 16 cm serta biomassa berkadar air 9,63%. Walaupun nyala api yang dihasilkan masih berwarna kuning kemerahan, namun kompor gasifikasi forced draft mampu menghasilkan energi termal hingga 3,43 kWth (kilowatt thermal) dengan temperatur nyala api tertinggi mencapai 933oC. Hasil penelitian menunjukkan bahwa kondisi operasi kompor gasifikasi sangat berpengaruh terhadap kinerja kompor sehingga disain kondisi operasi kompor perlu disesuaikan dengan kebutuhan pengguna kompor gasifikasi. Kata kunci: biomassa, kompor gasifikasi, forced draft, efisiensi termal